Nationalizing blackness : afrocubanismo and artistic revolution in Havana, 1920-1940 - Moore, Robin D., 1964- (Pitt Latin American series., 1997)
"An examination of Cuban society through the music of the 1920s-30s when it began to embrace Afro-Cuban culture. Traces how the African element of Cuban society became associated with national identity. Among topics examined are carnival bands, son music, cabaret rumba, and blackface theater shows. The highly documented volume is enhanced by the inclusion of relevant legislation concerning music, and a listing of sextets in Havana between 1920-45 by barrio"--Handbook of Latin American Studies, v. 58.